Operation rules of scraping technique - Hong Chen; Dongpan Fan; Jing He; Jin Zhao; Ling Tang (Wolters Kluwer Medknow Publications, 2022)
Traditional Chinese medicine scraping is a kind of natural therapy with a long history of simple and safe operation. It is easy to learn and tools are readily available, so that it has a very wide range of practical value. This paper introduces the definition and indications, function and standardization process of scraping technology, the technical operation specifications and matters needing attentions, as well as the application method of scraping technology, with a view to providing reference for clinical use of scraping technology in the treatment of cervical spondylosis, periarthritis of shoulder, lumbar muscle strain, hypertension, chloasma, and other diseases.